2013
DOI: 10.1002/ijc.28054
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of cell‐free miR‐198 as a diagnostic biomarker for lung adenocarcinoma‐associated malignant pleural effusion

Abstract: Circulating cell-free microRNAs (miRNAs) are potential cancer biomarkers. The aim of this study was to identify miRNAs that are differentially expressed between benign pleural effusion (BPE) and lung adenocarcinoma-associated malignant pleural effusion (LA-MPE). The expression level of cell-free miRNA was investigated in 107 patients with pleural effusion. Microarrays were used to screen 160 miRNAs in a discovery set comprising 20 effusion samples (ten BPEs and ten LA-MPEs). Real-time quantitative reverse tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 44 publications
0
56
0
Order By: Relevance
“…Thirty-three miRNAs were found to be altered by twofold in malignant effusions between longersurvival and shorter-survival groups, and the levels of miR-93, miR-100, miR-134, miR-151 and miR-345 were significantly associated with overall survival. Further studies by Han et al [126] identified miRNAs differentially expressed between benign pleural effusion samples and adenocarcinoma-associated malignant pleural effusion (LA-MPE). Microarray profiling showed that miR-198 was significantly downregulated in LA-MPE compared with benign pleural effusion samples.…”
Section: Circulating Micrornas Reviewmentioning
confidence: 97%
“…Thirty-three miRNAs were found to be altered by twofold in malignant effusions between longersurvival and shorter-survival groups, and the levels of miR-93, miR-100, miR-134, miR-151 and miR-345 were significantly associated with overall survival. Further studies by Han et al [126] identified miRNAs differentially expressed between benign pleural effusion samples and adenocarcinoma-associated malignant pleural effusion (LA-MPE). Microarray profiling showed that miR-198 was significantly downregulated in LA-MPE compared with benign pleural effusion samples.…”
Section: Circulating Micrornas Reviewmentioning
confidence: 97%
“…miRNAs are short non-coding RNAs which negatively or positively regulate gene expression in physiological and pathological conditions by binding to the 3′-UTR of their target mRNA, thereby inhibiting target gene translation into proteins. Effusion supernatants from lung, gastric and ovarian carcinoma have been shown to differ from benign specimens [39][40][41]. The latter study, in which miRNA content was analyzed in exosomes, small secreted vesicles involved in tumor signaling, was performed on archived material frozen at -80°C, including specimens stored for over 10 years [40].…”
Section: Other Ancillary Testingmentioning
confidence: 99%
“…In a previous study, we examined the differential expression of circulating miRNAs in BPE and LA-MPE samples using a peptide nucleic acid-based microarray [15]. The miRNA expression signatures were confirmed by RT-qPCR and cross-validated using an independent sample set.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of suitable genes for the relative quantification of miRNA expression is essential to avoid inaccurate results and to improve the comparability of gene expression data. We previously examined the expression of the selected miRNAs, two small nuclear RNAs (RNU6B and U6 snRNA), and two small nucleolar RNAs (RNU44 and RNU48) to identify the most stably expressed genes for use as reference genes in pleural effusion samples [15]. U6 snRNA was identified as the most stable reference gene in the BPE and LA-MPE samples; thus, the expression levels of the three miRNAs were normalized to those of U6 snRNA.…”
Section: Methodsmentioning
confidence: 99%